Efecto del ganado sobre la regeneración del bosque de Queñoa (Polylepis australis Bitt.) en las Yungas Australes del Noroeste argentino - Cuyckens, Griet An Erica (2021)
Introduction: Polylepis forest is an ecosystem stated with conservation priority and threatened by anthropogenic effects; extensive livestock is one of the most frequent disturbances in this forest. Objective: To study the effect of livestock on the early stages of regeneration of a queñoa (Polylepis australis Bitt.) forest. Materials and methods: Within a pure forest of P. australis at Parque Provincial Potrero de Yala, Jujuy, Argentina, densities of seedlings (˂1 year) and saplings (˃1 year and ˂30 cm) were measured in the presence (0.23 heads∙ha -1 ) and absence of livestock, for a year. Linear mixed models (normal distribution) were adjusted for density of seedlings and saplings. Data was analyzed with a Chi-square test (χ 2 ). Results and discussion: Presence of livestock had no impact on seedling density, but significantly decreased density of saplings (P < 0.001); in areas without livestock (10.58 ± 6.64 individuals∙m -2 ) was three times higher than with presence of livestock (3.17 ± 3.86 individuals∙m -2 ). Difference in density of seedlings and saplings was significantly (P < 0.001) over the years. This indicates that there is potential for natural regeneration, but livestock would affect stages after seedling emergence, representing a threat to the forest. Conclusion: This study provides important information for livestock management in mountain forests of P. australis. A long-term study of the effect of livestock on seedling and sapling density, and over the entire distribution range, is needed.